The Clinical Application of Robot-Assisted Ventriculoperitoneal Shunting in the Treatment of Hydrocephalus - Liu, De-feng; Liu, Huan-guang; Zhang, Kai; Meng, Fan-gang; Yang, An-chao; Zhang, Jian-guo (Frontiers in Neuroscience, 2021)
Background This work aims to assess the effectiveness and safety of robotic assistance in ventriculoperitoneal shunting and to compare the results with data from traditional surgery. Methods We retrospectively analyzed 60 patients who had undergone ventriculoperitoneal shunting, of which shunts were implanted using a robot in 20 patients and using traditional surgical methods in the other 40 patients. Data related to surgery were compared between the two groups, and the accuracy of the drainage tube in the robot-assisted group was assessed. Results In the robot-assisted surgery group, the operation duration was 29.75 ± 6.38 min, intraoperative blood loss was 10.0 ± 3.98 ml, the success rate of a single puncture was 100%, and the bone hole diameter was 4.0 ± 0.3 mm. On the other hand, the operation duration was 48.63 ± 6.60 min, intraoperative blood loss was 22.25 ± 4.52 ml, the success rate of a single puncture was 77.5%, and the bone hole diameter was 11.0 ± 0.2 mm in the traditional surgery group. The above are statistically different between the two groups (P < 0.05). Only one case of surgery-related complications occurred in the robot-assisted group, while 13 cases occurred in the traditional surgery group. There was no significant difference in the hospitalization time. In the robot-assisted surgery group, the average radial error was 2.4 ± 1.5 mm and the average axial error was 1.9 ± 2.1 mm. Conclusion In summary, robot-assisted implantation is accurate, simple to operate, and practical; the duration of surgery is short; trauma to the patient is reduced; and fewer postoperative complications related to surgery are reported.